Triple-helix formation by oligonucleotides containing the three bases thymine, cytosine, and guanine. - Giovannangéli, C (1992)
A homopurine-homopyrimidine sequence of human immunodeficiency virus (HIV) proviral DNA was chosen as a target for triple-helix-forming oligonucleotides. An oligonucleotide containing three bases (thymine, cytosine, and guanine) was shown to bind to its target sequence under physiological conditions. This oligonucleotide is bound in a parallel orientation with respect to the homopurine sequence. Thymines recognize A.T base pairs to form T.A.T base triplets and guanines recognize a run of G.C base pairs to form G.G.C base triplets. A single 5-methylcytosine was shown to stabilize the triple helix when incorporated in a stretch of thymines; it recognizes a single G.C base pair in a run of A.T base pairs. These results provide some of the rules required for choosing the more appropriate oligonucleotide sequence to form a triple helix at a homopurine-homopyrimidine sequence of duplex DNA. A psoralen derivative attached to the oligonucleotide containing thymine, 5-methylcytosine, and guanine was shown to photoinduce cross-linking of the two DNA strands at the target sequence in a plasmid containing part of the HIV proviral DNA sequence. Triplex formation and cross-linking were monitored by inhibition of Dra I restriction enzyme cleavage. The present results provide a rational basis for the development of triplex-forming oligonucleotides targeted to specific sequences of the HIV provirus integrated in its host genome.